2015
DOI: 10.1016/j.ajhg.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal-Recessive Intellectual Disability with Cerebellar Atrophy Syndrome Caused by Mutation of the Manganese and Zinc Transporter Gene SLC39A8

Abstract: Manganese (Mn) and zinc (Zn) are essential divalent cations used by cells as protein cofactors; various human studies and animal models have demonstrated the importance of Mn and Zn for development. Here we describe an autosomal-recessive disorder in six individuals from the Hutterite community and in an unrelated Egyptian sibpair; the disorder is characterized by intellectual disability, developmental delay, hypotonia, strabismus, cerebellar atrophy, and variable short stature. Exome sequencing in one affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
188
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(196 citation statements)
references
References 37 publications
7
188
0
1
Order By: Relevance
“…We examined N-glycan profiles in the serum of our Slc39a8-knockout mouse models using MALDI/time-of-flight mass spectrometric (MALDI-TOF-MS) analysis ( Figure 5, A-D). Compared with control mice, we observed that ZIP8-iKO mice had a decreased abundance of fully glycosylated N-glycan species (26.6% in WT vs. 16.2% in ZIP8-iKO mice) and an increased abundance of truncated N-glycan species, especially under-galactosylated N-glycan species including monosialo-monogalacto-biantennary glycans (1.0% in WT vs. 3.7% in ZIP8-iKO mice), asialo-monogalacto-biantennary glycans (0 in WT vs 1.7% in ZIP8-iKO mice), and asialo-agalactobiantennary glycans (0 in WT vs 1.4% in ZIP8-iKO mice). Similarly, compared with control mice, ZIP8-LSKO mice had a decreased abundance of fully glycosylated N-glycan species (41.0% in WT vs. 35.5% in ZIP8-LSKO mice) and an increased abundance of truncated N-glycan species, especially under-galactosylated N-glycan species monosialo-monogalacto-biantennary glycans (0.7% vs. 2.6%).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…We examined N-glycan profiles in the serum of our Slc39a8-knockout mouse models using MALDI/time-of-flight mass spectrometric (MALDI-TOF-MS) analysis ( Figure 5, A-D). Compared with control mice, we observed that ZIP8-iKO mice had a decreased abundance of fully glycosylated N-glycan species (26.6% in WT vs. 16.2% in ZIP8-iKO mice) and an increased abundance of truncated N-glycan species, especially under-galactosylated N-glycan species including monosialo-monogalacto-biantennary glycans (1.0% in WT vs. 3.7% in ZIP8-iKO mice), asialo-monogalacto-biantennary glycans (0 in WT vs 1.7% in ZIP8-iKO mice), and asialo-agalactobiantennary glycans (0 in WT vs 1.4% in ZIP8-iKO mice). Similarly, compared with control mice, ZIP8-LSKO mice had a decreased abundance of fully glycosylated N-glycan species (41.0% in WT vs. 35.5% in ZIP8-LSKO mice) and an increased abundance of truncated N-glycan species, especially under-galactosylated N-glycan species monosialo-monogalacto-biantennary glycans (0.7% vs. 2.6%).…”
Section: Resultsmentioning
confidence: 78%
“…***P ≤ 0.001, **P ≤ 0.01, and *P ≤0. (16)(17)(18). We examined N-glycan profiles in the serum of our Slc39a8-knockout mouse models using MALDI/time-of-flight mass spectrometric (MALDI-TOF-MS) analysis ( Figure 5, A-D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SLC39A8 mutations have also been associated with schizophrenia [42, 43], mental retardation [44], and with cerebellar atrophy [45] or cranial asymmetry [46] with accompanying dysmorphologies. Our reason for choosing those particular mouse tissues for HSeO 3 − uptake studies (Figure 4) reflected this growing list of ZIP8-related clinical disorders.…”
Section: Discussionmentioning
confidence: 99%